Application of Innovative Digital Medical Technologies of Bioquantum Medicine and Therapy in Elimination of Allergy Symptoms - Titarenko, Iurii (SSP Modern Pharmacy and Medicine, 2024)
In recent years, there has been an increasing integration of alternative medical technologies, particularly those involving digital medical technologies based on quantum and bioquantum medicine, frequency and wave therapy, and bioquantum therapy, for treating COVID-19, post-COVID, and long-COVID conditions as outlined in ICD-11. This study aimed to experimentally evaluate the latest digital medical technologies, specifically focusing on bioquantum therapy, for allergy treatment. A comprehensive review of existing literature on the application of bioquantum medicine in allergy therapy was conducted. The findings confirm that bioquantum therapy is an effective treatment option for mild to moderate allergies, significantly enhancing symptoms and overall quality of life. BICOM devices are recommended for managing mild to moderate allergies and associated complications. Furthermore, the study highlights that BICOM therapy is not only effective but also safe, with no serious adverse effects observed throughout the year-long study period. Given these promising results, it is recommended that healthcare professionals pursue specialized training, including master classes and continuous professional development in bioquantum medicine and therapy. Obtaining the necessary licenses and permits to work with BICOM devices is essential for ensuring the safe and effective application of this innovative treatment method. As the field continues to evolve, staying updated on the latest advancements in bioquantum medicine will be crucial for medical practitioners.